The geo-spatial distribution of childhood diarrheal disease in West Africa, 2008–2013: A covariate-adjusted cluster analysis. (August 2018) - Dunn, Gillian; Johnson, Glen D.
Highlights: Cluster analysis detects statistically significant areas of heightened risk of childhood diarrheal disease in West Africa. The clusters are partially explained by household and climatic factors such as mother's education and rainfall. Remaining clusters highlight areas where specific development and adaptation interventions are still required. Abstract: Diarrhea is a major cause of morbidity and mortality among children in West Africa. To determine whether there are areas of heightened risk and if so, how they may be influenced by household and climatic variables, we describe the geo-spatial distribution of childhood diarrhea in ten countries of West Africa for the period 2008–2013 using data from Demographic and Health Surveys. The purely spatial scan statistic was applied, where the observed diarrhea cases were modeled as a Poisson variable and were compared to expected cases predicted from non-spatial logistic regression. Covariate-adjusted cluster analysis detected statistically significant clusters ( p  < 0.05) in ten cities and thirteen largely rural areas. Areas with particularly high relative risk included Cotonou, Benin (7.16), and Kaduna, Nigeria (7.21). The study demonstrates the importance of development and adaptation measures to protect child health, and that these interventions should be tailored to meet the needs of specific populations.